If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (-11 + 2i) + -1(7 + -8i) = 0 Remove parenthesis around (-11 + 2i) -11 + 2i + -1(7 + -8i) = 0 -11 + 2i + (7 * -1 + -8i * -1) = 0 -11 + 2i + (-7 + 8i) = 0 Reorder the terms: -11 + -7 + 2i + 8i = 0 Combine like terms: -11 + -7 = -18 -18 + 2i + 8i = 0 Combine like terms: 2i + 8i = 10i -18 + 10i = 0 Solving -18 + 10i = 0 Solving for variable 'i'. Move all terms containing i to the left, all other terms to the right. Add '18' to each side of the equation. -18 + 18 + 10i = 0 + 18 Combine like terms: -18 + 18 = 0 0 + 10i = 0 + 18 10i = 0 + 18 Combine like terms: 0 + 18 = 18 10i = 18 Divide each side by '10'. i = 1.8 Simplifying i = 1.8
| 11+19= | | 15x-16=14x | | -9(12-12x)=-9(12+5x)+3x | | -5x+17=-33x | | 14+4x=43 | | 12x+5y+7y-3x= | | 5x-22=2x-4 | | -35x-7y=56 | | 2x-6+5x+3=46 | | A(3x+8)=-18x+b | | 40x=41x-2 | | 3x+17=4x | | -c=-22 | | 3+1=4x+1 | | 3x^3-5x^2+10x+9= | | q-11=9 | | 33x+-4=95 | | 3+1=7y+2 | | 2w+3-4w=17-(3w+2) | | 3+1=7y-2 | | 3=-12c+7 | | 3+1=7y-9 | | 15t-11t= | | 3=-15/2 | | 4x+4+4x=2(4x+2) | | 3/5=f/-5 | | 3/5=f-5/5 | | 13m+m= | | 7Y+25=56 | | 5(x+2)+x=6(x+3)-4x | | -4/7y=-8 | | 3x^3+6x^2-24x+15=0 |